New York : a chronological & documentary history, 1524-1970 - Furer, Howard B. (Dobbs Ferry, N.Y. : Oceana Publications, 1974)
Includes a chronology of historical events in the history of New York City from 1524 to 1970 and a selection of pertinent documents.
includes Bibliography
Keywords: New York (N.Y.) -- History -- Chronology; New York (N.Y.) -- History -- Sources; New York (N.Y.) -- History